Learning Range of Vocabularies in Foreign Languages - Rizayeva Kamola Shuxratovna (Genius Journals, 2022)
The article discusses the main features of vocabulary in learning foreign language. The author of the article analyses the importance hypothesis of vocabulary, main strategies, vital techniques, different instruction and various approaches (methods) theoretical and practically.
Keywords: Vocabulary; Strategy; Knowledge; Form